Zeroing in on Performance 2.0: From Serialization to Performative Enactments - Antti Lindfors (Folk Belief and Media Group of Estonian Literary Museum, 2022)
This article explores the notions of performativity and performance in digital environments from the combined perspective of linguistic anthropology and folkloristics. In order to bring these diverging conceptual, methodological, and disciplinary traditions into mutual contact, an intermediary heuristic term of "performative enactments" is introduced. Performative enactments are elaborated as events of communicative sign behavior that foreground and make use of the principle of performativity, although not performances proper in the sense of manifesting a specific "mode of communication" (Bauman 1984).